The Role of Perceived Risk in Moderating the Effects of Brand Image, E-WOM, and Brand Trust on Purchase Decision in Shopee Mall - Asnawir, Muh; Simanjuntak, Evi Rinawati (Jurnal Ilmiah Global Education, 2025)
This study aims to examine the moderating role of perceived risk in strengthening or weakening the influence of brand image, electronic word-of-mouth (e-WOM), and brand trust on consumer purchase decisions at Shopee Mall, as one of the largest marketplaces in Southeast Asia. The phenomenon of increasing online shopping amidst limited direct information and increasing information asymmetry requires a broader understanding of the psychological mechanisms in purchasing decision making. This study integrates four main theories: Signaling Theory, Trust Theory, Perceived Risk Theory, and Elaboration Likelihood Model (ELM) in one conceptual framework. Signaling Theory explains that brand image and e-WOM function as quality signals that reduce consumer uncertainty. Trust Theory positions brand trust as a psychological mechanism that bridges external signals and purchasing behavior. Perceived Risk Theory highlights that consumers consider potential losses subjectively in the context of online purchases. While ELM emphasizes that the formation of trust occurs through an elaborative process of external signals, especially in conditions of high involvement or risk. The research method used is quantitative with a survey approach to 447 Shopee Mall user respondents. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct effect, mediation by brand trust, and moderation by perceived risk. The results showed that brand image and e-WOM significantly influenced purchase decisions both directly and indirectly through brand trust. Perceived risk was shown to moderate the relationship between external signals and purchase decisions, but did not affect the influence of brand trust. These findings confirm that in the context of high-risk e-commerce, strong signals and brand trust are important factors in directing consumer decisions.